2016
DOI: 10.14260/jemds/2016/532
|View full text |Cite
|
Sign up to set email alerts
|

A Case Control Study of Intravenous Magnesium Sulphate in Treatment of Acute Organophosphate Poisoning

Abstract: BACKGROUNDTo study the efficacy of intravenous magnesium sulphate in the treatment of OPC poisoning and its outcome. To assess merits and demerits of use of MgSO4 with conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Trials under way include the search for medications already established for treatment of other conditions that may be repurposed for treatment of ALS ( Mehta et al, 2021 ). Mg 2+ therapies have been reported in previous experimental studies and clinical trials focused on mitigation of OP toxicity ( Bradley, 1986 ; Basher et al, 2013 ; Philomena et al, 2016 ; Vijayakumar et al, 2017 ; Jamshidi et al, 2018 ). The potential efficacy of magnesium has been considered previously in the context of nutrition or treatment of patients with ALS but clinical data from studies of MgSO 4 in both contexts have not been decisive ( Longnecker et al, 2000 ; Pamphlett et al, 2003 ; Fondell et al, 2013 ; Brvar et al, 2018 ; Aman et al, 2021 ; Kumar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trials under way include the search for medications already established for treatment of other conditions that may be repurposed for treatment of ALS ( Mehta et al, 2021 ). Mg 2+ therapies have been reported in previous experimental studies and clinical trials focused on mitigation of OP toxicity ( Bradley, 1986 ; Basher et al, 2013 ; Philomena et al, 2016 ; Vijayakumar et al, 2017 ; Jamshidi et al, 2018 ). The potential efficacy of magnesium has been considered previously in the context of nutrition or treatment of patients with ALS but clinical data from studies of MgSO 4 in both contexts have not been decisive ( Longnecker et al, 2000 ; Pamphlett et al, 2003 ; Fondell et al, 2013 ; Brvar et al, 2018 ; Aman et al, 2021 ; Kumar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, MgSO 4 therapy has proved clinically effective in treatment of eclampsia [11][12][13]. MgSO 4 therapies for OP poisoning have been reported in several clinical trials [6][7][8][9][10] and is now the subject of our ongoing study (CCBOC RCT; trial registration number NCT03925025).…”
Section: Implications For Acute Respiratory Failure After Insecticide Ingestionmentioning
confidence: 99%
“…At a molecular level, OP pesticides kill insects by inhibiting acetylcholinesterase (AChE) activity, which normally terminates the action of neurotransmitter at cholinergic synapses, including neuromuscular junctions [6][7][8][9][10]. When humans swallow these insecticides, they may experience symptoms and show signs of severe OP poisoning, including pulmonary edema, acute respiratory failure, abnormal weakness in proximal muscles (myasthenia), and neuromuscular synaptic dysfunction [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Review of titles and abstracts revealed 75 and 2187 papers of potential relevance in PubMed and China Academic Journals Full-text Database, respectively. The second stage, involving the screening of full-text articles for eligibility, revealed a total of 19 papers relevant to the question were identified: five preclinical studies [22][23][24][25][26], nine case reports or small case series [27][28][29][30][31][32][33][34][35], and five clinical studies, and trials [36][37][38][39][40]. We also obtained primary data from three unpublished clinical trials of MgSO 4 , providing data from a total of eight clinical studies and trials for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An observational clinical study compared the outcome of 69 patients presenting over three months who received MgSO 4 4 g within 24 h after admission with 64 control patients admitted over the previous three months who received only standard therapy [40]. This study reported reduced mortality and reduced need for mechanical ventilation in patients receiving MgSO 4 ( Table 2).…”
Section: Comparative Clinical Studiesmentioning
confidence: 99%